Effects of angico extract (Anadenanthera colubrina var. cebil) in cutaneous wound healing in rats - Pessoa,Wagner Soares (2012)
PURPOSE: To study the effects of the angico extract (Anadenanthera colubrina var. cebil) on the healing of rat skin. METHODS: Twenty adult rats were divided into four groups of five animals each, the G4, G7, G14 and G21, which corresponds to the respective postoperative days. Each group received two incisions on skin and subcutaneous tissue in the right and left antimere of the thoracic region, separated by a distance of 2 cm. The right lesion was treated daily with saline and the left with the angico alcoholic extract (5%). At the end of each experimental period, animals were euthanized and fragments of the wound area, together with the edges were removed, fixed in 10% formaldehyde solution and processed for paraffin embedding. In the histological sections with 5 µm of thickness, were carried out immunohistochemical methods for detection of blood vessels (VEGF) and stained with hematoxylin and eosin for morphological analysis. Statistical analysis was done by ANOVA and Tukey test (p<0.05). RESULTS: Morphological analysis showed larger fibroblasts and a higher concentration of collagen fibers in days 7 and 14 in wounds treated with the angico extract. Morphometric analysis demonstrated a significant increase in the number of blood vessels in both the seventh and 14th days (p<0.01) in wounds treated with the angico extract. CONCLUSION: The angico alcoholic extract (Anadenanthera colubrina var. cebil) induces the acceleration of wound healing in skin wounds of rats.